Synthesis and Evaluation of N-Arylsulfonylated Succinimides as Activity-Based Probes - Chvatal, Jo; Nguyen, Dat T.; Xie, Alexondra S.; Parsons, William H. (Synlett, 2025)
Activity-based protein profiling (ABPP) technology has served as a powerful platform for studying proteins for more than two decades. However, the further growth of this field depends on the development of new probe structures to expand the proportion of the proteome that can be studied using these methods. Inspired by previous reports of succinimide-containing covalent inhibitors for proteases, we synthesized a panel of potential probe structures with a succinimide reactive group and a terminal alkyne tag suitable for subsequent azide-alkyne click chemistry. Members of this panel with an N-arylsulfonyl linker produce labeling of both purified serine proteases as well as proteins in complex cellular lysates. We found that one of these probes labels the human rhomboid protease RHBDL2 at low micromolar concentrations and can be competed with active-site inhibitors. Our studies establish succinimide as a new reactive group for the development of activity-based probes and offer a new chemical tool for studying a class of enzymes with limited functional characterization.
Keywords: chemical probes; succinimides; click chemistry; activity-based protein profiling